2006
DOI: 10.1016/j.physleta.2005.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Classical and quantum contents of solvable game theory on Hilbert space

Abstract: A simple and general formulation of the quantum game theory is presented, accommodating all possible strategies in the Hilbert space for the first time. The theory is solvable for the two strategy quantum game, which is shown to be equivalent to a family of classical games supplemented by quantum interference. Our formulation gives a clear perspective to understand why and how quantum strategies outmaneuver classical strategies. It also reveals novel aspects of quantum games such as the stone-scissor-paper pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 10 publications
0
74
1
Order By: Relevance
“…An example is provided by the quantum games [41][42][43][44][45][46][47][48][49][50]. With the development of quantum game theory, it has been shown that many quantum games can be reformulated as classical games by allowing for a more complex game structure [51][52][53][54]. But, in the majority of cases, it is more efficient to play quantum game versions, as less information needs to be exchanged.…”
Section: Basic Ideas and Historical Retrospectivementioning
confidence: 99%
“…An example is provided by the quantum games [41][42][43][44][45][46][47][48][49][50]. With the development of quantum game theory, it has been shown that many quantum games can be reformulated as classical games by allowing for a more complex game structure [51][52][53][54]. But, in the majority of cases, it is more efficient to play quantum game versions, as less information needs to be exchanged.…”
Section: Basic Ideas and Historical Retrospectivementioning
confidence: 99%
“…In this form, we clearly see that both payoffs are composed of two components. First component, formerly termed as classical family 7) represents essentially classical payoff coming from "altruistic" modification of the game matrix. 18,19) Even with this modification, the payoffs are still constructed from factorizable probabilities p B , and therefore, payoffs will never exceed the limit (25).…”
Section: Pseudo-classical and Quantum Interference Componentsmentioning
confidence: 99%
“…In recent times much attention has been paid to the task of extending game theory concepts [3] to quantum mechanics [9][10][11][12][13][14][15][16][17][18][19]. Quantum games may be of interest given that its classical counterpart (CGT) has had such a phenomenal success.…”
Section: Our Goalsmentioning
confidence: 99%